Resource Allocation and Priority Setting in Health Care: A Multi‐criteria Decision Analysis Problem of Value?. (12th December 2016) - Angelis, Aris; Kanavos, Panos; Montibeller, Gilberto
Abstract: A methodological approach is needed for allocating health care resources in an efficient and fair way that gives legitimacy to decisions. Currently, most priority setting approaches tend to focus on single or limited benefit dimensions, even though the value of new health care interventions is multi‐dimensional. Explicit elicitation of social value trade‐offs is usually not possible and decision‐makers often adopt intuitive or heuristic modes for simplification purposes as part of an ad hoc decision‐making process which might diminish the reasonableness and credibility of the decisions. In this paper, we suggest that multi‐criteria decision analysis could provide a more comprehensive and transparent approach in health care to systematically capture decision‐makers' concerns, compare value trade‐offs and elicit their value preferences. We conclude that such methods could inform the development of a decision support system in health care, contributing towards more efficient, rational and legitimate resource allocation decisions. Abstract : The need has arisen for a rational methodological approach that can aid decision‐makers to understand, elicit and construct their preferences across a multitude of value concerns in a transparent way. Such an approach could help to improve the efficiency of resource allocation decisions across the field of health care with the ultimate goal of maximising societal welfare.